Niveles de eritropoyetina en pacientes con insuficiencia renal crónica que reciben hemodiálisis. Revisión sistemática - Quevedo Romero, Mayra Elizabeth (2024)
Renal failure (RF) is a clinical syndrome characterized by renal insufficiency and accumulation of metabolites and electrolytes in the body, it can be divided into two types: acute renal failure (ARF) or chronic renal failure (CRF). Acute renal failure occurs due to abrupt changes in renal function, while chronic renal failure is the result of a slow and progressive deterioration of renal function. Erythropoietin (EPO) is a glycoprotein hormone whose main function is the regulation of red blood cell production and thereby all processes related to aerobic energy formation. The present systematic investigation was executed in order to determine the levels of erythropoietin before and after the hemodialysis process in patients with CRF, in addition to correlate these levels with age and time of treatment. From the 10 studies included, it can be evidenced that there is consistency in the erythropoietin values, before hemodialysis, remaining in a range considered normal, even after hemodialysis, the connection between erythropoietin levels and the patients’ age shows a non-linear pattern, with its increases and decreases but within the normal range. Regarding the time of hemodialysis, a study revealed that in stage 4 CRF, erythropoietin levels were increased, this is attributed to the body's response to chronic kidney disease, linked to the stage of CRF, comorbidities and other biological or environmental factors